Populist collaborators : the Ilchinhoe and the Japanese colonization of Korea, 1896-1910 - Moon, Yumi (UPCC book collections on Project MUSE. History., 2013)
An empire invites local collaborators in the making and sustenance of its colonies. Between 1896 and 1910, Japan's project to colonize Korea was deeply intertwined with the movements of reform-minded Koreans to solve the crisis of the Choson dynasty (1392-1910). Among those reformers, it was the Ilchinhoe (Advance in Unity Society)-a unique group of reformers from various social origins-that most ardently embraced Japan's discourse of "civilizing Korea" and saw Japan's colonization as an opportunity to advance its own "populist agendas." The Ilchinhoe members called themselves "representatives of the people" and mobilized vibrant popular movements that claimed to protect the people's freedom, property, and lives. Neither modernist nor traditionalist, they were willing to sacrifice the sovereignty of the Korean monarchy if that would ensure the rights and equality of the people. Both the Japanese colonizers and the Korean elites disliked the Ilchinhoe for its aggressive activism, which sought to control local tax administration and reverse the existing power relations between the people and government officials. Ultimately, the Ilchinhoe members faced visceral moral condemnation from their fellow Koreans when their language and actions resulted in nothing but assist the emergence of the Japanese colonial empire in Korea. In Populist Collaborators, Yumi Moon examines the vexed position of these Korean reformers in the final years of the Choson dynasty, and highlights the global significance of their case for revisiting the politics of local collaboration in the history of a colonial empire.